2019
DOI: 10.1128/jvi.00364-19
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Inducible MicroRNA miR-128 Modulates HIV-1 Replication by Targeting TNPO3 mRNA

Abstract: The HIV/AIDS pandemic remains an important threat to human health. We have recently demonstrated that a novel microRNA (miR), miR-128, represses retrotransposon long interspaced element 1 (L1) by a dual mechanism, namely, by directly targeting the coding region of the L1 RNA and by repressing a required nuclear import factor (TNPO1). We have further determined that miR-128 represses the expression of all three TNPO proteins (transportins TNPO1, TNPO2, and TNPO3). Here, we establish that miR-128 also influences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…In primary neurons, the HIV Tat protein up-regulates miR-128-3p with concomitant suppression of the pre-synaptic SNAP25 protein, which may perturb neuronal activity [ 81 ]. In CD4+ T cells, miR-128-3p inhibits viral replication and delays virus spread by repressing the expression of TNPO3 [ 82 ], an observation similar to miR-128-3p mediated repression of retrotransposon long interspaced element 1 by targeting TNPO1 [ 83 ]. Notably, mature miR-128 is encoded by miR-128-1 and miR-128-2 [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…In primary neurons, the HIV Tat protein up-regulates miR-128-3p with concomitant suppression of the pre-synaptic SNAP25 protein, which may perturb neuronal activity [ 81 ]. In CD4+ T cells, miR-128-3p inhibits viral replication and delays virus spread by repressing the expression of TNPO3 [ 82 ], an observation similar to miR-128-3p mediated repression of retrotransposon long interspaced element 1 by targeting TNPO1 [ 83 ]. Notably, mature miR-128 is encoded by miR-128-1 and miR-128-2 [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNPO3 also known as transportin-SR2 is a carrier and the transporter of splicing factor in humans ( Maertens et al, 2014 ). Literature study suggests that TNPO3 mediates virus entry and particularly it is involved in Human immunodeficiency virus (HIV) (Bochnakian et al, 2019; De Iaco et al, 2013; Rice et al, 2020; Valle-Casuso et al, 2012 ). Additionally, clinical study suggests that it plays a role in primary biliary cirrhosis and systemic sclerosis ( Radstake et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, type I IFN-inducible miR-128 directly targets two sites in the transportin TNPO3 mRNA, considerably downregulating TNPO3 mRNA and protein expression levels. TNPO3 is a nuclear importer that is important for HIV-1 replication, and downregulation of this protein prevents viral replication [ 11 ]. Others have shown that miR-128 can inhibit HIV replication by directly targeting the 3′-UTR of the viral genome [ 110 ].…”
Section: The Role Of Mirnas In Viral Infectionmentioning
confidence: 99%